Self-healing functional semisolid electrolyte for battery and method for manufacturing the same
Patent Information
- Application Number
- KR1020250014549
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2045-02-05
Smart Images

Figure 112025013161946-PAT00006_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a functional self-healing semi-solid electrolyte for batteries and a method for manufacturing the same. More specifically, the invention involves adding an initiator, Azobisisobutyronitrile, a salt, Lithium bis(trifluoromethanesulfonyl)imide, a plasticizer, and a supporting electrolyte, Succinonitrile, and an additive, fluoroethylene carbonate, to a polymer monomer mixed with acrylic acid, acrylamide, and hexafluorobutylacrylate, mixing the mixture at 30°C for one hour, and then allowing the reaction to proceed at 70°C for two hours. This enables the product to not only possess a self-healing function through reversible hydrogen bonding but also excellent mechanical properties, electrical performance, and battery stability. Background Technology
[0002] Semisolid electrolytes possess an intermediate state between solid and liquid and are primarily used in battery systems such as lithium-ion batteries. In particular, semisolid electrolytes are known to provide structural stability similar to solids while maintaining ionic conductivity. Furthermore, compared to liquid electrolytes, they offer superior safety due to a lower risk of leakage, fire, and explosion. Their solid-like properties provide structural stability, allow them to adapt well to changes in battery volume, and generally maintain more stable performance at high temperatures. Additionally, these semisolid electrolytes are known to possess high ionic conductivity, high voltage stability, excellent interfacial contact, and low interfacial resistance.
[0004] The following (Patent Document 1) to (Patent Document 3) disclose technology regarding such semi-solid electrolytes.
[0005] (Patent Document 1) Korean Registered Patent No. 10-2610616
[0006] The purpose is to provide a non-aqueous electrolyte capable of improving the input / output characteristics of a secondary battery, and in particular, improving the lifespan and rate characteristics at high temperatures. Such a non-aqueous electrolyte comprises a solvated ionic liquid having an electrolyte salt with a sulfolane and / or its derivative, any low-viscosity organic solvent, and any negative electrode interface stabilizer, wherein the equilibrium vapor pressure of the low-viscosity organic solvent at room temperature is 1 Pa or more, and when the ratio of the moles of the solvated ionic liquid to the total moles of the low-viscosity organic solvent is X, and the ratio of the weight of the negative electrode interface stabilizer to the total weight of the solvated ionic liquid and the low-viscosity organic solvent is Y(%), Y ≤ 142.86X - 11.429 is satisfied.
[0008] (Patent Document 2) Korean Published Patent No. 10-2022-0148079
[0009] The present invention provides an electrolyte composite and a method for manufacturing the same, comprising: a solid electrolyte including an oxide-based solid electrolyte material; and an interface layer formed on at least one surface of the solid electrolyte; wherein, based on the total weight of the solid electrolyte, the oxide-based solid electrolyte material is included in an amount of 75% by weight or more, and the interface layer is composed of a gel polymer electrolyte. The electrolyte composite described above can be used as an electrolyte for a semi-solid battery and exhibit excellent electrochemical properties.
[0011] (Patent Document 3) Korean Registered Patent No. 10-2232148
[0012] The purpose is to improve the conductivity of the semi-solid electrolyte layer. The composition for solving the above problem is a semi-solid electrolyte layer comprising particles, a semi-solid electrolyte having a semi-solid electrolyte solution comprising a semi-solid electrolyte solvent and a low-viscosity organic solvent, and a semi-solid electrolyte binder, wherein the semi-solid electrolyte solution is supported on the particles, and the ratio of the low-viscosity organic solvent to 100% by weight of the mixed solvent of the semi-solid electrolyte solvent and the low-viscosity organic solvent is 10% by weight or more. Prior art literature
[0013] Korean Registered Patent No. 10-2610616 (Registration Date: Dec. 01, 2023) Korean Published Patent No. 10-2022-0148079 (Publication Date: Nov. 04, 2022) Korean Registered Patent No. 10-2232148 (Registration Date: Mar. 19, 2021) The problem to be solved
[0014] The present invention aims to provide a functional self-healing semi-solid electrolyte for batteries and a method for manufacturing the same, wherein the self-healing effect can be enhanced through reversible hydrogen bonding of the semi-solid electrolyte prepared by adding an initiator, Azobisisobutyronitrile, a salt, Lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI), a plasticizer and supporting electrolyte, Succinonitrile, and an additive, fluoroethylene carbonate, to a polymer monomer composed of acrylic acid, acrylamide, and hexafluorobutylacrylate, mixing at 30°C for 1 hour, and then allowing the reaction to proceed at 70°C for 2 hours. Furthermore, the present invention enables excellent mechanical properties, electrical performance, and battery stability in addition to this self-healing effect. means of solving the problem
[0015] A functional self-healing semi-solid electrolyte for a battery according to the present invention for achieving the above purpose comprises: a first step of obtaining a mixture by mixing PEGDA in an amount of 0.1 mol% of the total amount of polymer monomers with a polymer monomer composed of a molar ratio of AA : AM : HFBA = (10~15): (70~80): (10~15); a second step of adding succinonitrile to the mixture in a wt% ratio of the mixture : succinonitrile = 3:7; a third step of adding Li-TFSI at a concentration of 2M per unit volume of the succinonitrile; a fourth step of adding AIBN in an amount of 0.1 mol% of the total amount of polymer monomers to the mixture of the third step; a fifth step of adding FEC in an amount of 5% of the mass of the succinonitrile to the mixture of the fourth step; and a sixth step of mixing the mixture obtained in the fifth step at 30°C for 1 hour. and a seventh step of reacting the mixture obtained in the sixth step at 70°C for 2 hours; comprising,
[0016] The above polymer monomer and the component added to the above polymer monomer are, respectively,
[0017] AA: Acrylic acid;
[0018] AM: Acrylamide;
[0019] HFBA: Hexafluoro butylacrylate;
[0020] PEGDA: Poly(ethylene glycol) diacrylate (M n =10,000 g / mol);
[0021] Li-TFSI: Lithium bis(trifluoromethanesulfonyl) imide;
[0022] AIBN: Azobisisobutyronitrile;
[0023] Succinonitrile: Supporting electrolyte;
[0024] FEC: fluoroethylene carbonate;
[0025] It is characterized by being.
[0026] In addition, the present invention includes a functional self-healing semi-solid electrolyte for batteries characterized by being manufactured by the manufacturing method described above. Effects of the invention
[0027] The functional self-healing semi-solid electrolyte for batteries and the method for manufacturing the same according to the present invention have the following effects.
[0028] (1) When a semi-solid electrolyte is prepared according to the present invention, the prepared semi-solid electrolyte has a three-dimensional polymer network structure capable of reversible hydrogen bonding. The polymer network imparts mechanical properties to the semi-solid electrolyte, and at the same time, the self-healing function due to reversible hydrogen bonding can increase the functional and physical stability of the material.
[0029] (2) In addition, the semi-solid electrolyte is electrochemically stable and has a self-healing function, and is also effective in extending the battery's lifespan and improving performance due to its excellent stability at low and high overvoltages. Brief explanation of the drawing
[0030] [Fig. 1] is a block diagram showing the manufacturing process of a functional self-healing semi-solid electrolyte for batteries manufactured according to the present invention. [Fig. 2] is a photograph showing a functional self-healing semi-solid electrolyte for a battery manufactured according to the present invention. [Fig. 3] is a reaction diagram showing the synthesis reaction of a functional self-healing semi-solid electrolyte for batteries manufactured according to the present invention. [Fig. 4] is a graph showing an FT-IR spectrum to confirm the polymerization state by scanning the semi-solid electrolyte according to the present invention with a spectrometer. [Fig. 5(a)] shows a strain-stress curve indicating self-healing characteristics for a semi-solid electrolyte according to the invention, [Fig. 5(b)] shows a graph of strain recovery efficiency after self-healing over time, and [Fig. 5(c)] shows a graph of stress recovery efficiency after self-healing over time. [Fig. 6] is a graph comparing the electrical characteristics of a self-healing semi-solid electrolyte, which is an embodiment of the present invention, and a polymer electrolyte (PEGDA) without self-healing function, which is a comparative example, showing (a) ion conductivity, (b) electrochemical stability, (c) lithium ion transfer coefficient, and (d) spectroscopic results according to electrical impedance spectroscopy (EIS). [Fig. 7] is a graph showing the results of measuring overpotential and stability over time for a self-healing semi-solid electrolyte, which is an embodiment of the present invention, and a polymer electrolyte (PEGDA) without self-healing function, which is a comparative example. [Fig. 8] is a graph analyzing the performance of lithium-ion batteries for an example and a comparative example according to the present invention. Specific details for implementing the invention
[0031] Hereinafter, preferred embodiments of the present invention will be described in more detail with reference to the attached drawings. Prior to this, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, and should be interpreted in a meaning and concept consistent with the technical spirit of the present invention in accordance with the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0032] Therefore, the embodiments described in this specification and the configurations illustrated in the drawings are merely the most preferred embodiments of the present invention and do not represent all of the technical ideas of the present invention; thus, it should be understood that various equivalents and modifications that can replace them may exist at the time of filing this application.
[0034] [Method for manufacturing a functional self-healing semi-solid electrolyte for batteries]
[0035] The method for manufacturing a functional self-healing semi-solid electrolyte for a battery according to the present invention is to produce a semi-solid electrolyte by adding a polymer monomer (composed of acrylic acid, acrylamide, and hexafluorobutylacrylate), an initiator Azobisisobutyronitrile, a salt Lithium bis(trifluoromethanesulfonyl)imide, a plasticizer and a supporting electrolyte Succinonitrile, and an additive fluoroethylene carbonate in a predetermined order as shown in FIGS. 1 to 3, mixing for 1 hour at 30°C, and then reacting for 2 hours at 70°C, thereby enabling not only enhanced self-healing function but also improved mechanical properties, electrical performance, and battery stability.
[0037] Hereinafter, the configuration will be explained in more detail with reference to the attached drawings. Here, since the method for manufacturing a functional self-healing semi-solid electrolyte for batteries according to the present invention is carried out in seven steps, it will be explained here by dividing it into each step.
[0038] A. Stage 1
[0039] The first step is to obtain a mixture by mixing three types of polymer monomers in a fixed ratio as shown in [Figure 1], and adding PEGDA to these polymer monomers. Here, the types of each polymer monomer, their molar ratios, and the additional content of PEGDA are as shown in [Table 1] below.
[0040] ingredient Content polymer monomer AA AM HFBA Molby 10~15 70~80 10~15 PEGDA Mix 0.1 mol% of the total amount of polymer monomers 1. AA is acrylic acid. 2. AM is acrylamide. 3. HFBA is hexafluorobutylacrylate. 4. PEGDA is poly(ethylene glycol) diacrylate (M n =10,000 g / mol).
[0042] Here, acrylic acid and acrylamide possess structures capable of improving mechanical properties and self-healing characteristics through hydrogen bonding utilizing -COOH and -NH2 functional groups, respectively, which helps improve battery life and stability. Hexafluoro butylacrylate provides high chemical stability due to its fluorinated structure, which helps improve the electrochemical stability of the electrolyte as well as battery life and performance. Poly(ethylene glycol) diacrylate can form a three-dimensional network, increasing the mechanical strength of the electrolyte and providing structural stability, enabling the electrolyte to withstand physical forces or deformation.
[0044] B. Stage 2
[0045] The second step is to add succinonitrile to the mixture described above, as shown in [Fig. 1]. At this time, the succinonitrile is added in a wt% ratio of the mixture:succinonitrile = 3:7.
[0047] Here, the succinonitrile is a supporting electrolyte widely used as an additive for the anode. It forms a plastic crystal structure at room temperature to provide a pathway for Li ions to move, thereby stabilizing the structure of the anode or protecting its surface to suppress degradation, which in turn reduces the formation of transition metals and improves the battery's lifespan and performance. More importantly, it is intended to form a plastic crystal structure within the semi-solid electrolyte to provide a pathway for lithium ions to move.
[0049] C. Stage 3
[0050] The third step is to add Li-TFSI to the mixture of the second step, as shown in [Fig. 1]. At this time, the Li-TFSI is added at a concentration of 2M per unit volume of the succinonitrile.
[0052] Here, the Li-TFSI is "Lithium bis(trifluoromethanesulfonyl) imide," which provides an electrolyte with high ionic conductivity, thereby enabling lithium ions to move effectively within the electrolyte and improving the electrochemical performance of the battery. Additionally, Li-TFSI exhibits excellent thermal and chemical stability, allowing it to maintain stability for a long time without degrading battery performance, which helps to enhance the thermal stability of the electrolyte and extend the battery's lifespan. Furthermore, since Li-TFSI separates into lithium cations and TFSI=bis(trifluoromethanesulfonyl) imide anions within the electrolyte, it increases the ion concentration within the electrolyte, thereby increasing conductivity and accelerating the electrochemical reaction rate. Meanwhile, Li-TFSI stabilizes the network structure of the electrolyte, helping to form ion transport pathways, which contributes to improving the mechanical properties of the electrolyte and increasing ionic conductivity. Finally, Li-TFSI enhances ion conductivity at low temperatures, helping to improve battery performance at low temperatures and supporting the efficient operation of the battery in various environments.
[0054] D. Stage 4
[0055] The fourth step is to add AIBN to the mixture of the third step, as shown in [Fig. 1]. At this time, the AIBN is added in an amount of 0.1 mol% of the total amount of the polymer monomer.
[0057] Here, the AIBN is "Azobisisobutyronitrile" and is used as an initiator introduced into a reaction system to initiate a chain reaction. In particular, the AIBN plays a crucial role in improving battery performance and reliability by acting as a polymerization initiator, polymer network builder, conductive matrix formant, and providing thermal stability in the semi-solid electrolyte of the battery; thanks to these properties, AIBN is widely utilized in various electrochemical systems.
[0059] E. Stage 5
[0060] Step 5 is the step of adding FEC to the mixture of Step 4, as shown in [Fig. 1]. At this time, the FEC is added in an amount equal to 5% of the mass of Succinonitrile added in Step 2.
[0062] Here, the FEC is "fluoroethylene carbonate," an additive used to reduce the interfacial resistance of a battery and improve ion conductivity. This FEC is an organic compound that plays a role in improving the performance and stability of lithium-ion batteries. It possesses characteristics such as improved conductivity, chemical stability, SEI formation, and corrosion resistance, and prevents side reactions with lithium metal in environments above 50°C during the reaction. Thanks to these characteristics, FEC is widely used in various electrochemical systems.
[0064] Accordingly, in the present invention, the above FEC is added to prevent side reactions from occurring when lithium metal and succinonitrile come into contact in an environment of 50°C or higher during the reaction process.
[0066] B. Stage 6
[0067] Step 6 is a step of mixing the mixture obtained in Step 5 described above at 30°C for 1 hour, as shown in [Fig. 1].
[0069] G. Stage 7
[0070] Step 7 is a step of completing a semi-solid electrolyte by allowing the mixture mixed in Step 6 described above to be reacted at 70°C for 2 hours, as shown in [Fig. 1].
[0072] [Functional Self-Healing Semi-Solid Electrolyte for Batteries]
[0073] The present invention includes a functional self-healing semi-solid electrolyte for batteries manufactured by such a manufacturing method as shown in [Fig. 2]. Furthermore, as shown in [Figs. 3] and [Fig. 4], while this semi-solid electrolyte is manufactured by the manufacturing method according to the present invention, hydrogen bonding and lithium coordination bonding (Li + It includes a functional group capable of coordination bonding [Ion-Dipole Interaction].
[0075] In particular, as shown in [Fig. 4], a Fourier transform infrared (FT-IR) spectrometer was used to check whether the polymerization reaction for the semi-solid electrolyte according to the present invention was completely carried out at 4cm -1 This is a graph analyzed by scanning 32 times at the resolution. In [Fig. 4], the horizontal axis represents the wavenumber, the vertical axis represents the absorbance, the black line represents the FT-IR spectrum of the precursor (mixture) before reaction at 70°C, and the red line represents the FT-IR spectrum of the semi-solid electrolyte according to the present invention. As a result, the precursor before reaction at 70°C showed 1,625 cm⁻¹. -1 It can be seen that the C=C bond vibration peak appears in the reaction, but disappears in the semi-solid electrolyte after the reaction. This indicates that the synthesis was successful and a transparent electrolyte was produced, and the synthesized semi-solid electrolyte exhibits excellent mechanical properties to the extent of being free-standing, as shown in [Fig. 2].
[0077] Meanwhile, regarding the semi-solid electrolyte manufactured according to the present invention (Example) and the conventional semi-solid electrolyte without self-healing properties manufactured as shown in [Table 2] below (Comparative Example), the test results regarding (1) mechanical properties and self-healing efficiency, (2) electrical properties comparison, (3) overvoltage and stability, (4) battery performance comparison, and (5) battery stability are as follows.
[0078] Preparation method of the comparative example: 1) Prepare an electrolyte with a weight ratio of PEGDA and succinonitrile of 3:7. 2) Add Li-TFSI to achieve a concentration of 2M relative to succinonitrile. 3) Add 0.01 mol% of the total monomer amount of AIBN. 4) Add 5% of the mass of succinonitrile of FEC. 5) Mix at room temperature (20℃~25℃) for about 1 hour to prepare a clear solution.
[0080] Here, the example and the comparative example were each prepared by pouring 150 uL of solution into lithium metal based on Lithium 16pi, which is injected into a lithium battery of Coincell 2032 specifications, the example was reacted at 70°C for 2 hours, and the comparative example was reacted at 70°C for 30 minutes.
[0082] (1) Mechanical properties and self-healing efficiency
[0083] The comparison of self-healing efficiency was performed only on the examples, and the fracture strain-fracture stress curves were analyzed and compared as shown in [Fig. 5]; however, the comparative example did not possess self-healing functional groups and therefore could not recover mechanical properties after cutting. As a result, as shown in [Fig. 5(a)], a graph of the change in stress (KPa) on the vertical axis according to the change in strain (%) on the horizontal axis was obtained, and curves were obtained according to the change over time from the initial state (black line graph), namely 1 hour (red line), 9 hours (blue line graph), and 12 hours (green line graph).
[0085] The test at this time was conducted by completely cutting the polymer electrolyte with a razor blade and attaching the two pieces together at 25°C to demonstrate the ability to recover mechanical properties over time. As shown in [Fig. 5(a)], the polymer electrolyte of the comparative example showed a fracture strain-fracture stress of approximately 3,000% and 300 kPa, while the polymer electrolyte of the example that underwent 12 hours of self-healing showed a fracture strain-fracture stress of approximately 2,500% and 290 kPa, demonstrating that self-healing was successfully performed.
[0087] When separating the self-healing effect of strain and the self-healing characteristics of stress according to changes over time, as shown in [Fig. 5(b)] and [Fig. 5(c)], the self-healing efficiency over time is expressed as the ratio of stress and strain in the stress-stress curve after 1 hour, 9 hours, and 12 hours of self-healing after complete cutting, relative to the stress and strain of the undamaged sample. As shown in [Table 3] below, it can be seen that the self-healing performance is high, with 96% for stress and 84% for strain.
[0088] division 1 hour (h) 9 hours (h) 12 hours (h) Fracture strain 13% 53% 84% Fracture stress 32% 84% 96%
[0090] (2) Comparison of electrical characteristics
[0091] The electrical characteristics were compared using (a) ionic conductivity, (b) electrochemical stability, (c) lithium ion transport coefficient, and (d) electrochemical impedance spectroscopy.
[0092] (a) Ionic conductivity was measured by Electrochemical Impedance Spectroscopy (EIS) after constructing a sandwich structure consisting of stainless steel (SS) / semi-solid electrolyte / stainless steel (SS) with a semi-solid electrolyte inserted between two SS layers, as shown in [Fig. 6(a)]. The measurement was performed at a frequency of 10 6 Hz~10-1 It was conducted at Hz with an amplitude of 10mV, and 10 5 The ionic conductivity was calculated using the resistance value at. The ionic conductivity is It was calculated as follows (where R represents the resistance value of the measured EIS real part, l represents the thickness of the polymer electrolyte, and A represents the area). As a result, there was no significant difference in ionic conductivity between the example and the comparative example, and in the case of the example, it was found that it exhibited a high ionic conductivity of 2.6 mS / cm, which is higher than the standard ionic conductivity of 1 mS / cm for general solid electrolytes.
[0094] (b) Electrochemical stability voltage window, as shown in [Fig. 6(b)], is configured with a cell of Li / semi-solid electrolyte / SS and has a voltage range of 2.5V to 6V (V vs Li / Li + The electrochemical stability of the semi-solid electrolyte was measured using Linear Sweep Voltammetry (LSV) at a voltage scan rate of 10 mV / s. As a result, the example showed stability up to approximately 4.85 V, while the comparative example showed stability up to 4.5 V, indicating that the example is electrochemically more stable.
[0096] (c) The lithium ion transference number (Li transference number) is the proportion of Li ions in ion conduction, as shown in [Fig. 6(c)], and the cell is composed of Li / semi-solid electrolyte / Li and the frequency is 10 6 ~10 -1 Measurements were performed using Electrochemical Impedance Spectroscopy (EIS) at Hz with an amplitude of 10 mV. At this time, the cell was polarized by applying 10 mV for 6,000 seconds, followed by another EIS measurement, and then the lithium ion transfer coefficient (Li transferece number) was measured using the Bruce-Vincent method. As a result, the ethylene oxide (EO) group of PEGDA Li+ It interacts strongly with ions, which relatively slows down the lithium ion transfer rate. Although PEGDA is included in the example, it is contained in only a small amount (0.1 mol%) of the total monomer amount as a crosslinking agent, so the slowing down of the lithium ion transfer rate can be minimized.
[0098] (d) Electrochemical impedance spectroscopy was performed by configuring a cell with Li / semi-solid electrolyte / LFP as shown in [Fig. 6(d)], at a frequency of 10 6 ~10 -1 After measuring with EIS spectroscopy at Hz and an amplitude of 10 mV, the bulk resistance and charge transfer resistance were compared using a Nyquist plot. As a result, it was found that the bulk resistance and charge transfer resistance of the example were lower than those of the comparison example.
[0100] (3) Overvoltage and stability
[0101] In the solid electrolytes of the examples and comparative examples, lithium plating—in which the electrode surface is reduced to metallic lithium and plated during the battery charging process—and stripping—in which the electrode surface is oxidized to lithium ions and returns to the electrolyte during the battery discharging process—were evaluated. For this, the cell was constructed with a layered structure of Li / semi-solid electrolyte / Li and 0.1 mA / cm² 2 It was measured under a current density.
[0103] As a result, as shown in [Fig. 7], in the case of the comparative example, electrodeposition and peeling phenomena occur up to the initial 500 hours, but thereafter, the voltage value increases and becomes unstable due to the formation of lithium dendrites. In contrast, the example has a very low polarization voltage of 29.1 mV, which shows that rapid and stable lithium electrodeposition and peeling proceed at the interface between the electrode and the electrolyte. In addition, it can be seen that lithium electrodeposition and peeling proceed very stably for 1,500 hours without fluctuations in voltage value.
[0105] (4) Battery performance comparison
[0106] To analyze the performance of lithium-ion batteries using the semi-solid electrolytes of the examples and comparative examples, a Lithium Iron Phosphate (LFP) cathode was utilized, and the examples and comparative examples were fabricated into lithium metal batteries by inserting them between the LFP cathode and the lithium metal, respectively, and the results of the performance evaluation are shown in [Fig. 8]. Here, [Fig. 8(a)] shows a charge-discharge curve graph where the horizontal axis represents specific capacity and the vertical axis represents voltage; [Fig. 8(b)] shows a cycle performance graph of a lithium-ion battery where the horizontal axis represents cycle number and the vertical axis represents specific capacity; [Fig. 8(c)] shows a graph representing the specific capacity according to the charge-discharge rate of the example; and [Fig. 8(d)] shows a graph representing the specific capacity according to the cycle number of the comparative example.
[0108] As a result, as shown in FIGS. 8(a) to 8(c), the battery in the example operated without significant capacity degradation during rate retention tests at different charge and discharge speeds of 0.1C, 0.2C, 0.5C, and 1C, and it was observed that the original capacity of 0.1C was recovered when the speed was returned to 0.1C. The cycle performance test was conducted at 0.1C for the first 3 cycles and then measured at 1.0C; the 1.0C data is presented, and the semi-solid polymer electrolyte of the example demonstrates very stable cycle stability for 100 cycles at 1.0C.
[0110] Meanwhile, as shown in [Fig. 8(a)], [Fig. 8(b)], and [Fig. 8(d)], it can be seen that the semi-solid polymer electrolyte of the comparative example maintains its capacity at 1.0C for the first 10 cycles and then drops sharply.
[0112] (5) Battery stability
[0113] When comparing the results of [Fig. 8(b)] and [Fig. 8(d)] above, it can be confirmed that the example [Fig. 8(b)] proceeds stably with charging and discharging without a decrease in specific capacity at a rate of 1.0C, and the comparative example [Fig. 8(d)] is identical to the example except for the absence of the self-healing function, but since the specific capacity drops sharply after the initial 10 cycles, it can be determined that the self-healing function plays a major role in improving the stability of the battery.
Claims
Claim 1 A first step of obtaining a mixture by mixing PEGDA in an amount of 0.1 mol% of the total amount of polymer monomers with a polymer monomer composed of a molar ratio of AA : AM : HFBA = (10~15): (70~80): (10~15); a second step of adding succinonitrile to the mixture in a wt% ratio of the mixture : succinonitrile = 3:7; a third step of adding Li-TFSI at a concentration of 2M per unit volume of the succinonitrile; a fourth step of adding AIBN in an amount of 0.1 mol% of the total amount of polymer monomers to the mixture of the third step; a fifth step of adding FEC in an amount of 5% of the mass of the succinonitrile to the mixture of the fourth step; and a sixth step of mixing the mixture obtained in the fifth step at 30°C for 1 hour. and a seventh step of reacting the mixture obtained in the sixth step at 70°C for 2 hours; wherein the polymer monomer and the component added to the polymer monomer are, respectively, AA: Acrylic acid; AM: Acrylamide; HFBA: Hexafluoro butylacrylate; PEGDA: Poly(ethylene glycol) diacrylate (M n =10,000 g / mol);Li-TFSI: Lithium bis(trifluoromethanesulfonyl) imide;AIBN: Azobisisobutyronitrile;Succinonitrile: Supporting electrolyte;FEC: fluoroethylene carbonate; and the above 7th step is characterized by being performed while the mixture obtained in the above 6th step is in contact with lithium metal, thereby forming a method for manufacturing a functional self-healing semi-solid electrolyte for batteries. Claim 2 delete
Citation Information
Patent Citations
ELECTROLYTE COMPOSITE, MANUFACTURING METHOD THEREOF, and SEMI SOLID-STATE BATTERY COMPRISING ELECTROLYTE COMPOSITE
KR1020220148079A
Semi-solid electrolyte layer, battery cell sheet, and secondary battery
KR102232148B1
Non-aqueous electrolyte, semi-solid electrolyte layer, sheet for secondary battery and secondary battery
KR102610616B1
